Kepemimpinan Kepala Sekolah Islam di Era Transformasi Digital - Dewi Yaminah; Ade Rukmana; Lilis Mariyam; Nizma Armila; Mujahidin Mujahidin; Khaerul Khaerul (Jurnal Syntax Admiration, 2023)
Today, almost all fields, including in fields such as education, must implement digital systems and a leader is required to be responsive in this digital transformation era if he wants his institution or school to advance and develop. This article is about what are the challenges and opportunities for leaders in today's digital transformation era, and what leadership models are relevant in this digital era. The method used is qualitative approach in descriptive analysis using Scientific Literature StudiesThe method used is a qualitative method with data collection, using observation, in-depth interviews (indepth interview), and documentation studies. This article leads to the conclusion that the challenges and opportunities in the era of digital transformation must must be faced and filled by leaders in the digital age, especially the principals of Islamic institutions.absolutely be faced by leaders in the digital era.